Performance Analysis of Village Office Employees in Utilizing Information Technology for Community Administrative Services - Meiman Berkat Gea; Yupiter Mendrofa; Maria Magdalena Batee (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to analyze the use of information technology in improving administrative service performance at the Hilihambawa Village Office, Gunungsitoli Idanoi District, Gunungsitoli City. The study employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The findings indicate that the use of information technology at the Hilihambawa Village Office is not yet optimal. Although technological tools such as computers and the internet are available, their use is still limited due to a lack of training and understanding among employees, as well as infrastructure challenges such as unstable internet connections. Additionally, there is resistance to change among employees and insufficient outreach to the community regarding technology-based services. The study recommends enhancing digital literacy for village employees, improving technology infrastructure, and developing more targeted managerial strategies to support the optimal use of information technology in administrative services. The results are expected to serve as a reference for village governments and other researchers in developing more effective information technology implementation strategies in village administration.